2018
DOI: 10.1371/journal.pntd.0006731
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and demographic history of the Chagas disease vector Rhodnius nasutus (Hemiptera: Reduviidae) in the Brazilian Caatinga biome

Abstract: BackgroundRhodnius nasutus, a vector of the etiological agent Trypanosoma cruzi, is one of the epidemiologically most relevant triatomine species of the Brazilian Caatinga, where it often colonizes rural peridomestic structures such as chicken coops and occasionally invades houses. Historical colonization and determination of its genetic diversity and population structure may provide new information towards the improvement of vector control in the region. In this paper we present thoughtful analyses considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…It adapts to long-distance diffusion and is relatively sensitive to temperature changes, making it an ideal model for the evaluation of phylogeographic patterns and the assessment of the effects of topography and climatic cycles on the demographic history of East Asian reduviids and other indigenous insects [ 22 ]. Since sample collection is difficult, however, very few phylogeographic studies have focused on reduviid species [ 23 , 24 ]. Analyzing the genetic structure of this species helps test hypotheses concerning glacial migration across paleogeographic land bridges and vicariant range segregation caused by inter- and postglacial sea level increases.…”
Section: Introductionmentioning
confidence: 99%
“…It adapts to long-distance diffusion and is relatively sensitive to temperature changes, making it an ideal model for the evaluation of phylogeographic patterns and the assessment of the effects of topography and climatic cycles on the demographic history of East Asian reduviids and other indigenous insects [ 22 ]. Since sample collection is difficult, however, very few phylogeographic studies have focused on reduviid species [ 23 , 24 ]. Analyzing the genetic structure of this species helps test hypotheses concerning glacial migration across paleogeographic land bridges and vicariant range segregation caused by inter- and postglacial sea level increases.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that the broad ecological flexibility of R. ecuadoriensis was likely to correlate with similarly broad intraspecific variation, and set out to examine the signs of diversification and adaptation in this locally important vector species. To address both macro-scale diversity and micro-scale adaptations, we analyzed mitochondrial and nuclear DNA markers that have proven useful in similar study systems [ 5 9 , 11 , 12 , 15 17 , 19 , 72 74 , 80 84 ] and undertook a detailed qualitative/quantitative phenotypic assessment including head and forewing morphometrics [ 22 , 40 , 49 , 51 53 ]; we then used rich, specimen-specific ecological metadata (Additional file 1 : Table S1) to guide the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of all loci was successful in R. robustus and in 6-9 of the species of the prolixus group, while in species of the groups pallescens and pictipes, amplification of more than three loci was not achieved [111]. Subsequent studies have used microsatellites to analyze intraspecific genetic structure in different populations of R. pallescens [111,112], R. nasutus [36], R. ecuadoriensis [113], and R. prolixus [22]. In populations of R. pallescens, field and laboratory specimens have been compared, and laboratory colonies of R. pallescens showed a different genetic structure than their wild relatives [112].…”
Section: Microsatellitesmentioning
confidence: 99%
“…Studies of microsatellite markers in R. nasutus and R. ecuadoriensis showed that populations of these species from different geographic locations had genetic differences. For R. nasutus, four differentiated groups were revealed in eight geographic localities of the Brazilian Caatinga [36], and for R. ecuadoriensis, specimens in two biogeographically distinct localities of Ecuador had distinct genetic structures in association with other phenotypic differences [113]. Given its epidemiological importance, microsatellite markers were analyzed in wild and domestic populations of R. prolixus from Venezuela.…”
Section: Microsatellitesmentioning
confidence: 99%